Papillary squamotransitional cell carcinoma of the uterine cervix: A histomorphological and immunohistochemical study of nine cases - Anand, Mani (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Papillary squamotransitional cell carcinoma (PSCC) is a distinctive subcategory of squamous cell carcinoma of the uterine cervix. It has a propensity for local recurrence and late metastasis. Histologically, it can be misinterpreted as transitional cell carcinoma, or other papillary lesions of the cervix including squamous papilloma, verrucous carcinoma or cervical intraepithelial neoplasia grade 3 with papillary configuration. MATERIALS AND METHODS: Nine cases of PSCC of the uterine cervix were diagnosed on a cervical biopsy specimen on routine hematoxylin and eosin (H and E) stained sections. Their clinic-morphological features were analyzed. The cases were further evaluated immunohistochemically by cytokeratin 7 (CK7), cytokeratin 20 (CK20), p53 and Ki-67. RESULTS: The patients ranged in age from 35 years to 75 years; with abnormal uterine bleeding being the most common clinical presentation. All the cases showed papillary architecture with fibrovascular cores lined by multilayered atypical epithelium. Three cell types were observed: Clear, intermediate and basaloid. Stromal invasion was seen in five cases, whereas in the remaining four cases, the biopsy specimen was too superficial to definitely assess invasion. Immunohistochemically, eight cases were CK7(+)/CK20(–) and one case was CK7(–)/CK20(–). All nine cases showed nuclear accumulation of mutant p53. Moderate and high proliferative activity was observed in two and seven cases, respectively. Five of patients for whom follow-up information was available underwent radical hysterectomy and two of them were disease free 18 months following treatment. CONCLUSION: PSCC of the uterine cervix are a clinicomorphologically distinct group of cervical lesions that display a morphologic spectrum. They are potentially aggressive malignant tumors that should be distinguished from transitional cell carcinoma and other papillary lesions of the uterine cervix.